Démocratie délibérative en Grande-Bretagne : La rhétorique participative à l’épreuve - Jean-Philippe FONS (E-REA)
This chapter aims at analysing the modes of governance in contemporay Britain. Among other things we intend to define the role of the State and of citizens in the social and economic regulation developed under New Labour since 1997. Simultaneously we contend that the rhetoric of deliberative democracy has altered the participation of citizens in British society.